AN EMPIRICAL ANALYSIS OF WORKING STATUS OF MIGRANT WORKERS IN CHHATTISGARH (International Journal of Food and Nutritional Sciences, 2023)
Generally, people migrate in search of employment or for better livelihood from one place toanother place. They are the important segment of any country’s economy hence the migrantworkers have a fair share in the process of development. According to their skill and workingexperience they are engaged various types of works. This paper tries to understand the engagementof the migrants in various types of works in the state of Chhattisgarh. The available secondary dataof census 2024 is used to assess the employment engagement of these workers as per their agegroup. It is observed that a large percentage of migrants in Chhattisgarh are engaged as mainworkers and are in the age group of 35 to 39. Due to the enforcement of act of child prohibition inhazardous work, the engagement of children in the age group of 0 to14 is very less. The same kindof results have been observed in this paper. It is also observed that most of the migrants in the stateof Chhattisgarh are not engaged in any kind of work, hence are classifies as non-workers. In thecategory of marginal workers, the highest percentage engagement is of those migrants who are inthe age group of 20 to 24 age. This paper tries to fill the gap of studies conducted in the workengagement of migrants according to their age groups.